Análise de métodos diagnósticos para rastreio da sarcopenia e adiposidade abdominal em mulheres com câncer de mama não metastático - Souza, Vanusa Felício de (2023)
During treatment for breast cancer (BC), there can be a loss of strength and muscle mass and a reduction in physical performance, defined as sarcopenia. Another change observed is an increase in body adiposity, especially visceral adipose tissue (VAT), which is associated with worse clinical outcomes in this population. Given these implications, this study aimed to: 1. compare the diagnostic accuracy of SARC-CalF and SARC-CalF with calf circumference (CC) adjusted for body mass index (BMI) in assessing the risk of sarcopenia; 2. evaluate the association between anthropometric and imaging measures of central adiposity in women with BC. This is a cross-sectional study of women diagnosed with BC within 12 months and aged over 30 years in outpatient care. The risk of sarcopenia was assessed using the SARC-F, SARCCalF and SARC-CalF questionnaires with CC adjusted for BMI. Abdominal adiposity was assessed by waist circumference (WC) and VAT, obtained by dual-energy X-ray absorptiometry (DXA). Anova, Kruskal-Wallis, Chi-square and Fisher's exact tests were applied for the bivariate analyses. Spearman's correlation analysis and multivariate linear regression models were applied to verify the association between WC and VAT with reference to age group. The significance level adopted was 5%. Considering SARC-F ≥2 as a reference, SARC-CalF showed a sensitivity of 9.10%, specificity of 81.4%, AUC of 0.86 [(0.79 - 0.93); p <0.001]. The SARC-CalF with CC adjusted for BMI showed a sensitivity of 41.8%, specificity of 83.1% and AUC of 0.70 [(0.60 - 0.80) p<0.001]. When EWRS-F ≥4 was used as a reference, SARC-CalF showed a sensitivity of 16.6%, specificity of 75.0% and AUC of 0.84 [(0.77 - 0.91); p<0.001]. The SARC-CalF with CC adjusted for BMI showed a sensitivity of 55.5%, specificity of 79.4% and AUC of 0.80 [(0.69- 0.91) p<0.001]. There was a strong correlation between WC and VAT in adult women (r= 0.83; p= <0.001) and elderly women (r=0.70; p= <0.001). VAT was also correlated with appendicular skeletal muscle mass index (ASMI) (r= 0.51; p= <0.001), percentage body fat (%BF) (r=0.73; p<0.001) and BMI (r=0.78; p<0.001). WC correlated with ASMI (r= 0.60; p<0.001), BMI (r= 0.84; p<0.001) and %BF (r= 0.84; p<0.001). After adjusted models, WC remained associated with VAT in adults (β= 2.60; CI= 1.31-3.87; P= <0.001) and elderly women (β = 1.70; CI= 0.43-2.97; p= 0.010). This study showed that the SARC-Calf with CC adjusted for BMI has a better predictive capacity for assessing the risk of sarcopenia and the WC proved to be a reliable indicator and a safe alternative to the VAT for identifying visceral fat in BC women, and both are simple, fast and non-invasive.